Pharmacokinetics of Cephradine Suspension in Infants and Children - Ginsburg, Charles M. (1979)
The pharmacokinetics of cephradine suspension were studied in 16 infants and children who were 13 months to 8 years and 3 months of age (means age, 3.5 years). Mean peak concentrations of 21.3 and 9.9 μg/ml were achieved at 30 min after administration of 60-mg/kg doses to fasting and nonfasting patients. The area under the serum concentration-time curve was 26% larger in fasting than in fed subjects. The half-life of cephradine in serum was 0.8 and 1.0 h in fasting and fed groups, respectively. Antimicrobial activity was detected in 49% of all salivary samples; in 75% of specimens, the concentrations were less than the 50% minimum inhibitory concentration for most pneumococci and group A streptococci. Urinary concentrations of cephradine ranged from 28 to 8,760 μg/ml and were independent of feeding status.